Concluding remarks for advances in ion spectroscopy Faraday Discussion. (6th June 2019) - Simons, Jack
Abstract : Because the Introductory Lecture of this Faraday Discussion emphasized the recent history and exciting developments in the fields of experimental methods and applications of gaseous ion spectroscopy, these Concluding Remarks are, by design, directed somewhat more toward the roles played by theory. Abstract : Because the Introductory Lecture of this Faraday Discussion emphasized the recent history and exciting developments in the fields of experimental methods and applications of gaseous ion spectroscopy, these Concluding Remarks are, by design, directed somewhat more toward the roles played by theory. In discussing both the experimental and theoretical studies of gaseous ions, it is important to recognize and appreciate the delicate balance workers in the field are pursuing in terms of methodological/tool development and applications to current-day pressing problems in chemistry, physics, materials science, and biology. Without both components of modern research in this field, progress will not be efficient. Substantial discussion is included about the reductive approach that is commonly used to attempt to connect studies of ions in the gas phase ( i.e., as isolated species) with properties of these ions as they exist in nature. Issues of how small a model system can be, to what extent surroundings/solvation can be addressed, and how our experimental or theoretical tools might limit us are all discussed in some detail. The current ability of theory to assist in the interpretation of experimental spectral data on gaseous ions is discussed, as are several of the most pressing limitations of theory on this front. Finally, the author offers his thoughts about what advances/improvements in theory are needed and the outlook for when they might be expected, and urges the experimental community to remain in close contact with theory groups developing new methods so that progress can be optimized.